European monetary integration - Sinn, Hans-Werner; Widgrén, Mika; Köthenbürger, Marko (CESifo seminar series., 2004)
Studies examining the policy challenges posed by European monetary integration, including asymmetry problems and fiscal concerns. The success of European monetary integration--called by the editors of this CESifo volume "one of the most far-reaching, real world experiments in monetary policy to date"--Is not assured. Policy makers have been forced to deal with challenges posed by formulating a uniform monetary policy for countries with asymmetric business cycles and economies in different stages of development as well as with the fiscal and financial implications of a unified currency. The contributors to European Monetary Integration, all prominent economists and scholars, combine theoretical analysis and policy recommendation in their examination of these difficulties. In the first three chapters they consider issues raised by asymmetry problems, including imperfect labor and goods markets, the problem of monetary policy objectives when "one size does not fit all," and the possibility of a bias toward smaller countries in the "one country, one vote" constitutional structure of the European Central Bank. In the last three chapters, they discuss fiscal concerns, including the distribution of seignorage revenues and the interaction of European Central Bank monetary policies and asset price dynamics